Pharmacokinetics and Pharmacodynamics of Gamithromycin Treatment of Pasteurella multocida in a Murine Lung Infection Model - Yang, Qingwen; Liu, Xuesong; Zhang, Chenghuan; Yong, Kang; Clifton, Alancia Carol; Ding, Huanzhong; Liu, Yun (Frontiers in Pharmacology, 2019)
Gamithromycin is approved for the treatment and prevention of bovine respiratory disease (BRD), which is caused mainly by Mannheimia haemolytica, Pasteurella multocida, Histophilus somni and Mycoplasma species. In this study, multiple dosage regimens was administered to the neutropenic mouse lung infection model in order to investigate the pharmacokinetic/pharmacodynamic (PK/PD) parameters of gamithromycin treatment of Pasteurella multocida and to further define the PK/PD parameter that best correlates with the efficacy of gamithromycin against Pasteurella multocida. The PK characteristics of gamithromycin were analyzed after a single subcutaneous (s.c.) injection (1, 3, 6, and 9 mg/kg). The concentration-time profiles of unbound (f) gamithromycin in plasma samples were analyzed by non-compartmental analysis. The main PK parameters of gamithromycin for the area under concentration-time curve from 0 to 24 h (f AUC0–24 h) and the peak drug concentration (f Cmax) values ranged from 0.86 to 8.42 µg·h/mL and from 0.55 to 5.69 µg/mL, respectively. The PD values were calculated based on multiple s.c. injections over 24 h (1, 3, 6, and 9 mg/kg at 6, 8, 12, and 24 h, respectively; total dosage 1–36 mg/kg). The minimum inhibitory concentration (MIC) of gamithromycin against Pasteurella multocida in mice serum was 0.15 μg/mL. Analysis of PK/PD indices using the inhibitory effect Emax model indicated a strong correlation (R2=0.9624) between the f AUC0–24 h /MIC ratio and various antibacterial effects. The area under the unbound concentration-time profile over 24 h to MIC ( f AUC0–24 h/MIC) predicted for bacteriostatic action, 1-log10 reduction, 2-log10 reduction and 3-log10 reduction were 56.77 h, 90.18 h, 143.06 h, and 239.44 h, respectively. These in vivo data may facilitate gamithromycin dosage optimization against Pasteurella multocida in veterinary medicine.